Differences in reporting somatic complaints in elderly by education level - Stankunas, M (2013)
Aim: To evaluate the association between somatic complaints and education level among elders in selected European countries. Methods: Cross-sectional study among randomly selected community dwelling persons aged 60–84 years from seven cities in Europe: Ancona (Italy), Athens (Greece), Granada (Spain), Kaunas (Lithuania), Stuttgart (Germany), Porto (Portugal) and Stockholm (Sweden). Somatic complaints were measured with the 24-item version of the Giessen Complaint List (GBB-24). A regression analysis was done to investigate the association between education and somatic complaints. Results. The mean GBB-24 scale was 16.3±14.9. The most common complaints were pain in joints and limbs (29.6%), back-pain (24.1%), heaviness or tiredness in the legs (19.1%) and general tiredness (15.7%). Respondents with less than primary education reported higher levels of somatic symptoms compared to those with university degree. A regression analysis showed that higher education (OR=0.69) and being male (OR=0.48) were associated with a decreased risk for high levels of somatic complaints, and the opposite for older age (OR=1.03) and being single/divorced/window (OR=1.28). Conclusions: The results indicate that less educated elders are more likely to expressed somatic complaints.